Relative Mastery among Nurses - Majeed, Azhar Muhammad; Abd, Shahid Ibrahim (Journal of Cultural Analysis and Social Change, 2026)
Studies indicate that relative mastery reflects an individual's ability to control and manage their thoughts, emotions, and behaviors. It plays a fundamental role in various life domains, influencing academic achievement, social interactions, and overall well-being. Learning professional mastery is considered one of the essential competencies for the healthcare system and its workers to successfully face the current challenges. The study aimed to investigate: 1. The level of relative mastery among nurses. 2. The significance of differences in relative mastery according to the following variables: Gender (male - female)/ Age (20-35), (36 and above)/Years of service (1-15), (16 and above)/ Educational attainment (secondary - bachelor). 3. The interaction effect of gender, age, years of service, and educational attainment on relative mastery. To achieve these objectives, the researchers adopted the scale of Schkade and Schultz (2003), which defines relative mastery as the phenomenon through which behaviors indicating changes or improvements in occupational adaptation are identified, including individuals' perceptions of their effectiveness, competence, and satisfaction regarding their responses to professional challenges. The study sample consisted of 400 nurses selected using stratified random sampling from 8 hospitals in the Health Directorates of Rusafa, Karkh, and the Medical City. The sample was categorized by gender, age, years of service, and educational attainment. Data were analyzed using the SPSS software, and the researchers reached the following conclusions: 1. Nurses showed a low level of relative mastery with a mean score of 53.05, which is below the hypothetical mean of 81. 2. A statistically significant difference in relative mastery by gender was found in favor of males (F = 5.83 > 3.83, p < 0.05). 3. A statistically significant difference by age was observed in favor of the 36 and above group (F = 27.64 > 3, p < 0.05). 4. A statistically significant difference by years of service was found in favor of those with 16 years or more (F = 23.6 > 3, p < 0.05). 5. A statistically significant difference by educational attainment was found in favor of bachelor's degree holders (F = 20.8 > 3.83, p < 0.05). 6. No significant interaction was found between the variables (gender, age, years of service, educational attainment). 1. Strengthen collaboration between the Ministry of Health and civil society organizations to utilize assessment tools to diagnose low relative mastery among nurses in hospitals and health centers and to organize training programs by the relevant authorities to improve the quality of nursing services in Iraq. 2. Coordinate with the Ministries of Education and Higher Education to guide students in nursing schools and colleges toward professional values through conferences, seminars, and workshops, helping them overcome pressures and ethical distress to achieve mastery in the nursing profession. Conduct future studies on relative mastery and its relationship with other variables not addressed in this research, such as ethical dilemmas, moral climate, personal values and beliefs, and organizational support.